Feminist Digital Literature in Italy. Delays, Breakthroughs and Exceptions - Liliosa Azara (Asparkía)
As the digital world has broadened the spectrum of digital and digitised archives, in Italy, digital feminist literature has seen a delayed implementation, alongside some major achievements. It is due to the democratisation of knowledge that sources and accounts, previously the preserve of academics, have become accessible to a broad and diversified readership. The launching of digitisation projects has enabled a reinterpretation of the genesis, evolution and dynamics of the emancipation and feminist movements. The article provides a comparative analysis of digital feminist literature by considering two cases, namely the UDI (Unione Donne in Italia) (1944), the largest Italian women’s organisation, and its Noi Donne magazine, along with the neo-feminism of the seventies and the Effe magazine, representative of the various elements in the transnational movement.